Experiences of Dying Animals: Parallels With End-Of-Life Experiences in Humans - Sheldrake, Rupert; Smart, Pam; Nahm, Michael (Journal of Scientific Exploration, 2023)
There has recently been an increased interest in end-of-life experiences (ELEs) in humans, but ELEs in non-human animals have not yet been assessed. In this paper, we present findings from a study we performed to collect and analyze reports about remarkable behavioral aspects of animals during their last phase of life. After public appeals in which we asked for reports about ELEs in animals, we received numerous responses from pet owners. We were able to group these experiences into specific categories, which we termed the last goodbyes, last visits, last rally, retreating into solitude, unusual premonitions of death, somatic surprises, terminal lucidity in animals, and potential near-death visions in animals. We present 43 case reports pertaining to these different categories. Many of them show striking similarities to remarkable behavior reported from dying people. This similarity between animal and human ELEs might be a sign of a common physiology underpinning such experiences and could also increase the recognition that animals share an inner life similar to that of humans during all phases of life. This could lead to a more respectful treatment of pets, as well as of animals in farms, zoos, and in the wild. However, as our study was of preliminary character and only the first of its kind, we encourage further systematic research in this field. In the Supplementary Material, we publish 71 additional cases for those who would like to study more examples.